Hubungan Dukungan Keluarga dan Lama Menjalani Hemodialisa terhadap Tingkat Kecemasan Pada Pasien Gagal Ginjal Kronik - Oktavianingsih Oktavianingsih; Elvie Tresya; Indri Sarwili (Jurnal Ventilator, 2025)
Chronic kidney failure or chronic kidney disease (CKD) is a non-communicable disease that has increased the prevalence of mortality and morbidity in the last 20 years. The prevalence according to RISKESDAS in 2013 showed CKD was 2% and increased to 3.8% (739,208) in 2018. Dialysis is a kidney replacement therapy (TPG) which is used to prevent kidney deterioration. TPG carried out throughout life will change the patient's life physically, cognitively, psychologically, socially, and spiritually. When undergoing dialysis, patients experience ambivalent feelings towards the hemodialysis process that they are currently undergoing, namely positive feelings in the form of happiness when washing freely and negative feelings including feelings of anxiety and worry about the disease they are experiencing. This study aims to determine the existence of family relationships and the length of undergoing hemodialysis on the level of anxiety in patients with chronic kidney failure at Hospital X Jakarta. The method used is quantitative analysis with a cross-sectional research design on 45 respondents with the Spearman Rank correlation test. The results show a significant relationship between family support and the length of time undergoing hemodialysis with the level of anxiety in chronic kidney failure patients with values of ? = 0.001 < ? and ? = 0.007 < ?, correlation coefficient (rs) = 0.472 and (rs) = -0.397, so H0 is rejected and H1 is accepted with a moderate level of significance. In conclusion, family support and the length of time undergoing hemodialysis have a moderate relationship to anxiety levels in chronic kidney failure patients.